Analisis Konsep Kebijakan Publik (Studi Kasus Bantuan Dana Operasional Sekolah (BOS) - Sri Devi Monica (Universitas Dr. Soetomo Surabaya, 2021)
This study describes an analysis of the public policy of the BOS Fund program. The purpose of this research is to know the concept of implementation and aspects that influence the public policy of Dana BOS program. This study uses a qualitative descriptive method. Data collection techniques with observations and documents - documents adapted to the research. The concept of implementing public policies, especially the BOS Fund, is to independently finance school operations. The BOS policy on the one hand helps public/private schools in operational financing. The BOS funds also help parents pay for school fees. There are several things that become obstacles in the implementation of policies 1) Communication, 2) Resources, 3) Disposition, 4) Bureaucratic Structure.